Dynamics of pH, Ferrum and Mangan, and Phosphorus on Newly Opened Paddy Soil having High Soil Organic Matter on Rice Growth - Ladiyani Retno Widowati; . Sukristyonubowo (UNIVERSITY OF LAMPUNG, 2012)
Research had been carried out at the Research and Soil Testing Laboratory and Greenhouse of Soil Research Institute, Bogor using newly opened paddy soil from Pesisir Selatan districts, West Sumatra (one year old). Total treatments tested were 12 which were combination of farmer rate, NPK recommendation (½×; ¾×; 1½×), straw compost (½×; ¾×; 1½×), and dolomite. The trial was conducted using a completely randomized design with three replications. This research had been prepared in two units, one unit for observing plant response to nutrient management and another unit for incubation trial with the same treatment placed in the greenhouse. Rice cultivar used was IR-42 in accordance to the preferred varieties of local farmers. The sampling method for measuring the solubility of Fe2+ and Mn2+, as well as the availability of PO43- was by centrifuge 50 g mud samples from the incubation pots then separated clear extract using filter paper. The observation results on dynamics of pH, Fe2+, Mn2+ and PO4-3 mainly occured in 1 to 14 days after submerging (incubation). After 14 days soil reaction had reached thermodynamic sequence of oxidation-reduction processes, the PO43- more available and pH of the soil reached the peak. The optimum dose of NPK fertilizer obtained 0.875 NPK or equal to 175 kg of urea, 87.5 kg of SP-36 and 87.5 kg KCl ha-1. The highest number of hills achieved from straw compost treatment 1½ organic matter (OM) or 3 tons with an increase of 20%. Application of ameliorant dolomite increased the number of tillers about 2-3%, but insignificantly different with no dolomite treatment.